THE EFFECT OF RECIPROCAL TEACHING METHOD IN READING COMPREHENSION ON HORTATORY EXPOSITION TEXT OF ELEVENTH GRADE STUDENTS OF SMA KRISTEN KALAM KUDUS PEKANBARU - Wita Wirawati; Syofia Delfi; Dahnilsyah Dahnilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to find out the significant effect of Reciprocal Teaching Method on reading hortatory exposition text of the second year students of SMA Kristen Kalam Kudus Pekanbaru academic year 2018/2019. The selected sample was XI MIPA 1. The sample was selected by using random sampling technique. This research used pre-experimental research design of one group pre-test post-test and collected the data by using test on hortatory exposition text. The test this research was multiple choice test consisted of five option (a/b/c/d/e) The result of the study was found that the mean score of the pre-test was 74.75 while the post-test was 83.87 Therefore it can be concluded that there is a significant effect of Reciprocal Teaching Method on reading comprehension of the second year student of SMA Kristen Kalam Kudus Pekanbaru. Based on the result of data analysis, it can be concluded that there is a significant difference in students’ achievement before and after being thought by Reciprocal Teaching Method. It can be stated that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. Reciprocal Teaching Method gives positive and enjoyable learning environments in the classroom. It also enhanced the students’ participation and interaction during the learning process. Students comprehended the story completely by the prediction that helped students to develop their reading and concentrating ability through Reciprocal Teaching Method.Key Words: Effect, Reciprocal Teaching Method, Reading Comprehension.